Exploring Students’ Speaking Anxiety in New Normal Era : Descriptive Study - Wulandari, Triyani; Wardhani, Ika Desy; Sabartono, Ribut (English Education Department, Faculty of Teacher Training and Education, Islamic University of Jember, 2023)
This research aims to find out how high the level of anxiety is among students, especially English Language Learners, they really experience difficulties in speaking which causes self-confidence and anxiety problems. Storytelling can improve speaking skills but poses difficulties due to previously exclusive online learning. Storytelling significantly benefits English learning in the new normal era, boosting confidence and outcomes. While students generally express interest, some remain hesitant. Inconsistent media use by teachers needs rectification. Anxiety persists, especially in remote learning due to physical restrictions and limited social interaction. Teachers must creatively engage students, utilize technology, and foster a supportive environment to address these issues and optimize storytelling's benefits.